2010
DOI: 10.1186/1471-2407-10-164
|View full text |Cite
|
Sign up to set email alerts
|

Increased Rac1 activity and Pak1 overexpression are associated with lymphovascular invasion and lymph node metastasis of upper urinary tract cancer

Abstract: BackgroundLymphovascular invasion (LVI) and lymph node metastasis are conventional pathological factors associated with an unfavorable prognosis of urothelial carcinoma of the upper urinary tract (UC-UUT), but little is known about the molecular mechanisms underlying LVI and nodal metastasis in this disease. Rac1 small GTPase (Rac1) is essential for tumor metastasis. Activated GTP-bound Rac1 (Rac1 activity) plays a key role in activating downstream effectors known as Pak (21-activated kinase), which are key re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
54
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 27 publications
(51 reference statements)
9
54
0
2
Order By: Relevance
“…A robust line of studies have provided evidence supporting the crucial role of Rac1 in human cancers. Rac1 expression was associ- ated with invasion and metastasis in urothelial carcinoma (19). Rac1 promoted colon cancer progression through promotion of cell proliferation, survival and migration (36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A robust line of studies have provided evidence supporting the crucial role of Rac1 in human cancers. Rac1 expression was associ- ated with invasion and metastasis in urothelial carcinoma (19). Rac1 promoted colon cancer progression through promotion of cell proliferation, survival and migration (36).…”
Section: Discussionmentioning
confidence: 99%
“…Rac1 regulates a diverse spectrum of cellular functions including tumorigenesis (11), angiogenesis (12,13) and metastasis (11,14,15). Overexpression of Rac1 occurs in several different types of tumors including breast (16,17), colon (18), bladder (19), and gastric cancer (20,21). Rac1 overexpression was observed in metastatic gastric (21), breast (15), prostate (22), bladder upper urinary tract cancer (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAKs are subdivided into two groups based on structural and functional features 28,29 ; group-1 consists of PAK1, PAK2 and PAK3, while group-2 consists of PAK4, PAK5 and PAK6. Although PAK1 has been implicated in the recurrence of urothelial cancer of the bladder 30 and progression of upper tract urothelial cancer 31 , the role of other PAKs have not been well characterised in urothelial oncogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the expression of these proteins in tumor samples was significantly higher than non-tumoric samples, and it was also reported that expression of Rho, Rac1 and cdc42 proteins in advanced stages of cancer is higher than in the early stages of cancer [34]. Expression of Rac1 and PAK proteins, a potent effector of Rac1, was evaluated on four groups including tumor and non-tumoric tissue, metastatic and normal lymph nodes in the upper urinary tract cancer and the results showed that expression levels of active Rac1 and PAK in tumor and metastatic lymph nodes were significantly higher than their levels in samples non-tumoric [35]. Considering that active Rac1 can mediate looseness of adhesion connections and subsequently accelerate migratory phenotype [13,14].…”
Section: Discussionmentioning
confidence: 99%